How Noodle Delineation Influences the Urine pH - Sultana, Mehwish (International Journal of Pharmaceutical & Biological Archive, 2024)
The intent of the present study was to associate the urine pH with the noodles rendering. The pH of urine is acidic, alkaline, or neutral. If the pH of your urine is less than seven, the pH is acidic. If the pH is more than seven, the pH shows alkalinity. However, if the pH is seven, the pH is neutral. The pH in the body is maintained by the kidney. The glomerular filtrate of blood is usually acidified by the kidneys from a pH of approximately 7.4 to a pH of about 6 in urine. Normally, the pH in our body is maintained by the kidney primarily through the reabsorption of sodium, hydrogen, and ammonium ions. If the amount of sodium is more than the pH of urine, it is acidic. If the amount of bicarbonate-carbonic acid is excess, the pH of urine is basic or alkali. Noodles are mostly used in China as a most favorite dish. Noodles are a good source of vitamins, minerals, carbohydrates, and lipids. It is closured from the present study that there is no influence of noodle delineation on urine pH.